The Use of Twitter as an Interactive Learning Tool Within a Postgraduate Public Health Course: A Pilot Study. (June 2021) - Ronto, Rimante; Bhatti, Alexandra; Chau, Josephine
Twitter has gained attention in recent years as a tool to use in higher education to enhance students' learning, engagement, and reflective writing. This study explored public health students' perceptions on the usefulness of Twitter as a learning tool, engagement with their peers, staff, and the broader public health community. Participants were Master of Public Health students from a public university based in Sydney, Australia. A mixed methods approach was used combining content analysis of tweets, an online survey and two focus groups. Students were asked to engage with Twitter by reflecting on each week's teaching content and by liking and replying to their peers' tweets. Participation and engagement in this task were high initially and declined toward the end of semester. Most student tweets aligned with topics taught during the semester. Survey and focus group data indicated most students had positive views on using Twitter and reported finding engagement with Twitter beneficial in obtaining current information on health promotion news and trends, increasing their professional networks and allowing them to connect with their peers and teaching staff. Results indicate Twitter is a promising interactive approach to enhance public health students' engagement and overall learning experience, as well as being useful for professional networking. Larger scale empirical studies are needed to investigate the impact of the use of social media platforms such as Twitter to various learning outcomes longitudinally and beyond this course.